Evaluation of a maternal, neonatal and child health intervention package in a rural district of Pakistan: a quasi-experimental study - Habib, Muhammad Atif; Black, Kirsten I.; Greenow, Camille Raynes; Mirani, Mushtaq; Muhammad, Sajid; Shaheen, Fariha; Khadka, Monika Christofori; Vondeling, Annette; Ariff, Shabina; Soofi, Sajid Bashir (International Journal Of Community Medicine And Public Health, 2019)
Background: Pakistan is among the countries which have the highest maternal, neonatal and child mortality rates. Immediate efforts are required to enable Pakistan to achieve the health related sustainable development goals. The continuum of care interventions can substantially reduce the mortality burden, however local evidence to implement them is lacking in Pakistan. We implemented the maternal, neonatal and child health intervention package comprised of health facility strengthening, capacity building, continuum of care interventions and community mobilization and evaluated its effectiveness on maternal, neonatal and child health care practices and neonatal mortality. Methods: The intervention package was delivered through existing public health system in a rural district of Pakistan. We used a quasi-experimental design to assess the impact of interventions. Baseline and end line surveys were conducted and neonatal mortality was considered as the primary outcome measure. Data were analysed using bivariate and difference and difference analysis techniques. Results: We found a reduced risk of neonatal mortality (RR 0.704; 95% CI 0.557-0.889; p=0.0033), in intervention areas compared to control area. For secondary outcomes; including mortality for infants and under five children, antenatal care, skilled birth attendance, institutional deliveries, postnatal care, delayed bathing, inappropriate cord care practices, birth asphyxia, exclusive breastfeeding and immunization a significant difference (p<0.001) was observed in the intervention area compared to control area. Conclusions: This study provides local evidence from Pakistan that effective methods for delivering MNCH interventions within the existing health infrastructure can improve the MNCH outcomes especially in the rural areas.